MicroRNAs and their targets: recognition, regulation and an emerging reciprocal relationship - Pasquinelli, Amy E. (Nature reviews. Genetics, 2012)
Key Points MicroRNAs (miRNAs) function as 21–24-nucleotide-long guides that regulate the expression of mRNAs containing complementary sequences. Although plant miRNAs typically base-pair perfectly to target sites, animal miRNAs form imperfect duplexes with target sequences, complicating the ability to predict direct targets. Numerous computational and experimental methods have been developed for studying miRNA target recognition and regulation. In plants and animals, miRNAs usually repress target expression by inducing mRNA deadenylation and degradation or by inhibiting translation. Many factors, including target site context, RNA-binding proteins and modifying enzymes, influence the ability of the miRNA complex to bind and regulate specific targets. Base pairing between an miRNA and its target can influence the stability of the miRNA, resulting in increased miRNA levels in some cases and stimulated degradation in others. Coding and non-coding RNAs can function as competing endogenous RNAs (ceRNAs) that bind miRNAs, sequestering them from binding and regulating other RNAs. miRNA 'sponges' have been engineered to titrate specific miRNAs to study their functions in vivo . The new understanding that miRNAs can both regulate and be regulated by target interactions raises many questions regarding the definition of a miRNA target and the functional outcome of miRNA targeting in vivo . MicroRNAs are key regulators of gene expression. Emerging evidence points towards a reciprocal relationship between microRNAs and their targets and for roles of non-target RNAs and proteins in this crosstalk. MicroRNAs (miRNAs) have emerged as key gene regulators in diverse biological pathways. These small non-coding RNAs bind to target sequences in mRNAs, typically resulting in repressed gene expression. Several methods are now available for identifying miRNA target sites, but the mere presence of an miRNA-binding site is insufficient for predicting target regulation. Regulation of targets by miRNAs is subject to various levels of control, and recent developments have presented a new twist; targets can reciprocally control the level and function of miRNAs. This mutual regulation of miRNAs and target genes is challenging our understanding of the gene-regulatory role of miRNAs in vivo and has important implications for the use of these RNAs in therapeutic settings.